Evolving Speaking Strategies in Arabic Learning: Insights from Oxford’s Strategy Inventory in Indonesia - Moh Sholeh Afyuddin; Eka Nur Isnayny Syifa’i Qulub; Isy Firrohmah Al Izzah; Maziyyatul Muslimah (Journal of Arabic Language Teaching, 2025)
This study aims to examine the learning strategies used by students of the Arabic Language Education Study Program, Faculty of Tarbiyah, State Islamic Institute of Kediri in the maharah kalam course using the language learning strategy classification verified by Rebecca Oxford. The results of this study can provide an overview for language learners, teachers, and practitioners about the learning strategies that are widely used in learning maharah kalam. This study employs a mixed-method approach with a sequential explanatory design. Quantitative data were collected through a questionnaire adapted from the Strategy Inventory for Language Learning (SILL), while qualitative data were gathered through in-depth interviews with selected respondents to explore the concrete forms of learning strategies employed. The results of the study indicate that students use various learning strategies, both direct (such as cognitive and compensatory strategies) and indirect (such as metacognitive and social strategies). Metacognitive strategies, such as planning and self-evaluation, and social strategies, such as collaborating with friends, are the most dominant strategies used. The researcher also found a lack of understanding and application of affective strategies among students, which impacts their low self-confidence in speaking Arabic in public. Penelitian ini bertujuan untuk menelaah strategi pembelajaran yang digunakan oleh mahasiswa Program Studi Pendidikan Bahasa Arab, Fakultas Tarbiyah, Institut Agama Islam Negeri Kediri dalam mata kuliah maharah kalam dengan menggunakan klasifikasi strategi pembelajaran bahasa yang dikembangkan oleh Rebecca Oxford. Hasil penelitian ini diharapkan dapat memberikan gambaran bagi para pembelajar bahasa, pendidik, dan praktisi mengenai strategi pembelajaran yang paling banyak digunakan dalam pembelajaran maharah kalam. Penelitian ini menggunakan pendekatan campuran (mixed method) dengan desain penjelasan berurutan (sequential explanatory design). Data kuantitatif dikumpulkan melalui angket yang diadaptasi dari Strategy Inventory for Language Learning (SILL), sedangkan data kualitatif diperoleh melalui wawancara mendalam dengan responden terpilih untuk menggali bentuk konkret penerapan strategi pembelajaran yang digunakan. Hasil penelitian menunjukkan bahwa mahasiswa menggunakan berbagai strategi pembelajaran, baik strategi langsung (seperti strategi kognitif dan kompensasi) maupun strategi tidak langsung (seperti strategi metakognitif dan sosial). Strategi metakognitif, seperti perencanaan dan evaluasi diri, serta strategi sosial, seperti kerja sama dengan teman, merupakan strategi yang paling dominan digunakan. Peneliti juga menemukan kurangnya pemahaman dan penerapan strategi afektif di kalangan mahasiswa, yang berdampak pada rendahnya kepercayaan diri mereka dalam berbicara bahasa Arab di depan umum.